العربية الهجينة في دول الخليج العربي: المسؤولية الشخصية والعدالة الاجتماعية / Arabic Pidgin in the Gulf States: Personal Responsibility and Social Justice - Abdulrahman Alfahad (مجلة الدراسات اللغوية والأدبية (Journal of Linguistic and Literary Studies), 2023)
ملخص البحث: يتوافد عدد هائل من العمال الأجانب الذين لا يتحدثون العربية إلى منطقة الخليج كل عام؛ حيث يمكثون فيها سنوات طويلة يختلطون بأهلها ويتواصلون معهم؛ غير أن الملاحظ أن هذا الزمن الطويل لم يكسب هؤلاء العمال اللغة المحكية في تلك الدول؛ إذ يتواصل أفراد هذه المنطقة معهم بلغة هجينة توصف بأنها أقل درجة وتقديراً من اللغة الدارجة. تحاول هذه الدراسة أن تتقصى تلك اللغة المستعملة من جانبين: تحليل جانبها التركيبيالصرفي، ومن ثم محاولة تقصي الآثار المترتبة على استعمالها من منظور العدالة الاجتماعية، مستعينةً بذلك بمنهج اللسانيات الاجتماعية في تسجيل تلك اللغة المستعملة، ومن ثم تحليلها لمعرفة تراكيبها في نماذج واسعة من هذه اللغة الهجينة المستعملة بين المواطنين السعوديين والعمال الأجانب. ولعل أبرز النتائج التي توصلت إليها هذه الدراسة أن هذه اللغة ليست مرحلة أولية من اللغة الأم قد تتطور لاحقاً بالتواصل مع مستعلمي اللغة الدارجة، بل أصبحت قائمة على نظام مطرد في تركيبها واستعمالها، وهذا ما يفسر لنا أسباب بقاء هذه اللغة الهجينة، واستعمالها لسنوات دون تطور حتى بين أولئك الذين عاشوا في هذه البلدان سنوات طويلة؛ أما الجانب الآخر المرتبط بالعدالة الاجتماعية، فإن لوم هذه الشريحة على ضعف اكتساب اللغة الدارجة أو رميهم بالكسل وضعف الرغبة هو أمر لا يخلو من التحيز الاجتماعي، فالخروج من هذا النظام اللغوي ليس أمراً بأيدي هؤلاء العمال، فالمجتمع الأكبر المسيطر يفرضها عليهم من خلال التواصل من خلالها، فأصبح تعلم اللغة العربية من خلال ما يسمى بالانغماس اللغوي (Immersion) ليس أمراً متاحاً، كما أن الانخراط في دروس تعليمية لاكتسابها أمرٌ غير وارد؛ حيث ضيق الوقت، والتركيز على كسب لقمة العيش، وضعف الموارد المالية جميعها التي تكالبت عليهم. الكلمات المفتاحية: لسانيات اجتماعية، لغة هجينة، مسؤولية شخصية، عدالة اجتماعية، سياسة لغوية. Abstract: A large number of foreign workers who do not speak Arabic flock to the Gulf region every year; where they stay there for many years, mixing with its people and communicating with them. However, it is noticeable that during this long period, these workers did not acquire the spoken language in those countries, as people of this region communicate with them in a hybrid language (pidgin language), which is described as having a lower class and appreciation (Lower Prestige) than the local language. This study attempts to investigate the language used from two aspects: analyzing its morphological and structural aspect, thereby trying to investigate the effects of its usage from the perspective of social justice. It relies on the sociolinguistic approach by recording the used language, and then analyzing it to find out its structures in wide models of this hybrid language used between Saudi citizens and foreign workers. One of the most important findings of this study is that this language is not a preliminary stage of the mother tongue. It might be developed later through communication with the users of local language, but rather it has become a standalone system in its structure and usage. This explains to us the reasons for the survival and use of this hybrid language for years without development, even among those who have lived in this country for many years. As for the other aspect related to social justice, blaming these workers for failing to acquire the local language, or accusing them of laziness and lack of desire is bound to social prejudice. Getting out of this linguistic system is not a choice for these workers, as the larger dominant society imposes it on them by communicating through it, so learning Arabic language through what is called linguistic immersion is not an option for them. Moreover, engaging in educational lessons to acquire Arabic is also out of the question; as time constraints, focus on earning a living, and poor financial resources all weighed on them. Keywords: sociolinguistics, pidgin language, personal responsibility, social justice, language policy. Abstrak: Saban tahun, sebilangan besar pekerja asing yang tidak boleh berbahasa Arab menjadikan rantau Teluk Arab sebagai tempat mereka mencari rezeki. Mereka tinggal di sana bertahun-tahun, bergaul dengan rakyatnya dan berkomunikasi dengan mereka. Walau bagaimanapun, selama mereka menetap di sana, mereka tidak menguasai bahasa pertuturan rakyat setempat. Ini kerana penduduk rantau ini berkomunikasi dengan mereka dalam bahasa Pijin, yang digambarkan sebagai dialek yang lebih rendah kualitinya berbanding dialek Arab yang digunakan rakyat setempat. Kajian ini menyelidik bahasa yang digunakan dari dua aspek: menganalisis aspek morfologi dan strukturnya, dan kemudian cuba mengkaji kesan penggunaannya dari perspektif keadilan sosial. Kajian ini menggunakan kaedah sosiolinguistik dalam merekodkan bahasa yang digenean, dan kemudian menganalisisnya untuk mengetahui strukturnya dalam model luas bahasa hibrid ini yang digunakan antara warga Saudi dan pekerja asing. Antara dapatan kajian ini ialah bahasa Pijin ini bukanlah peringkat awal bahasa ibunda. Ia mungkin berkembang kemudian melalui komunikasi dengan penutur dialek tempatan. Bahasa ini boleh dianggap mempunyai sistem yang mantap dalam komposisi dan penggunaannya. Ini menjelaskan kepada kita mengapa bahasa Pijin ini mampu bertahan, malah digunakan selama bertahun-tahun tanpa mengalami apa jua bentuk perubahan, hatta di kalangan mereka yang telah tinggal di negara-negara ini selama bertahun-tahun. Bagi aspek lain yang berkaitan dengan keadilan sosial, menyalahkan golongan ini kerana lemah menguasai dialek setempat atau menuduh mereka malas belajar adalah merupakan prasangka sosial. Keluar daripada sistem linguistik setempat ini bukanlah pilihan yang dilakukan para pekerja ini. Masyarakat umumlah yang memaksa menggunakan bahasa ini melalui komunikasi. Oleh itu, mempelajari bahasa Arab melalui kaedah pergaulan bukanlah satu pilihan. Selain itu, menguasai dialek setempat melalui pengajian rasmi juga bukan suatu yang mudah. Selain kekangan masa, tumpuan untuk mencari rezeki, dan kekurangan sumber kewangan adalah antara faktor yang membebankan mereka. Kata kunci: sosiolinguistik, bahasa hibrid, tanggungjawab peribadi, keadilan sosial, dasar bahasa.